Indonesian and United States of American Economic Partnership Agreement Effect - Tajerin Tajerin (Universitas Islam Indonesia, 2009)
The paper analyzes fisheries trade effects from the implementation of Indonesian and the UnitedStates of American Economic Partnership Agreement (IUSEPA). The analysis is performed on theintegrated world trade databases owned by World Trade Organization, United Nations Conferenceon Trade and Development, and United Nations Statistics Division, using Wits software packagedeveloped by the World Bank. The result indicates that in the future, Indonesian government as aparty that will conduct bilateral economic partnership agreement with the United states, needs topropose or negotiate fishery import tariffs that imposed by the United States ranges from 0 to 7percent.Keywords: Bilateral economic agreement, fisheries, trade effect